Alveolar ridge preservation in post-extraction sockets using concentrated growth factors: a split-mouth, randomized, controlled clinical trial - Elayah, Sadam Ahmed; Younis, Hamza; Cui, Hao; Liang, Xiang; Sakran, Karim Ahmed; Alkadasi, Baleegh; Al-Moraissi, Essam Ahmed; Albadani, Mohammed; Al-Okad, Wafa; Tu, Junbo; Na, Sijia (Frontiers in Endocrinology, 2023)
Aim: The aim of this clinical trial was to assess the impact of autologous concentrated growth factor (CGF) as a socket filling material and its ridge preservation properties following the lower third molar extraction. Materials and Methods: A total of 60 sides of 30 participants who had completely symmetrical bilateral impacted lower third molars were enrolled. The primary outcome variables of the study were bone height & width, bone density and socket surface area in coronal section. Cone beam computed tomography images were obtained immediately after surgery and three months after surgery as a temporal measure. Follow-up data were compared to baseline using Paired & Unpaired t‑test. Results: CGF sites had higher values in height and width when compared to Control sites (Buccal wall 32.9±3.5 vs 29.4±4.3 mm, Lingual wall 25.4±3.5 vs 23.1±4 mm, and Alveolar bone width 21.07±1.55vs19.53±1.90 mm) respectively. Bone density showed significantly higher values in CGF sites than in control sites (Coronal half 200±127.3 vs -84.1±121.3, Apical half 406.5±103 vs 64.2±158.6) respectively. There was a significant difference between both sites in reduction of periodontal pocket. Conclusion: CGF application following surgical extraction provides an easy, low-cost, and efficient option for alveolar ridge preservation. Thus, the use of CGF by dentists during dental extractions may be encouraged, particularly when the alveolar ridge preservation is required.